Automated evaluation of the surface point quality in dimensional X-ray computed tomography - Müller, Andreas; Butzhammer, Lorenz; Wohlgemuth, Florian; Hausotte, Tino (Technisches Messen, 2020)
X-ray computed tomography (CT) enables dimensional measurements of numerous measurands with a single scan, including the measurement of inner structures. However, measurement artefacts complicate the applicability of the technology in some cases. This paper presents a methodology to assess the surface point quality of computed tomography measurements without the requirement of a CAD model. Measurement artefacts lowering the surface point quality can therefore automatically be detected. The correlation of quality values with the random measurement error is demonstrated. The presented method can in principle be used to weight single fit points to reduce the measurement uncertainty of CT measurement
Keywords: Industrial X-ray computed tomography; surface point quality; volume data; segmentation